2015
DOI: 10.1080/15332845.2015.1008386
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Generation Perceptions of Value-Centered Leadership Principles

Abstract: The purpose of this study was to identify Millennial generation hospitality students perceptions of value-centered leadership principles for the purpose of better aligning future leader expectations with hospitality industry workforce realties. Data for this study were collected through survey instrumentation administered to a purposeful sample of Millennials in the Northeast-Midwest regions of the United States ( n = 276). Findings indicated Millennials value leaders that are more orientated toward people rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 21 publications
2
38
1
1
Order By: Relevance
“…They were found to value loyalty less than other cohorts (Gibson et al, 2009) but also to desire dedication for their supervisors and their employers (Sessa et al, 2007). Millennials seem to enjoy collaboration and value being on teams (Maier et al, 2015), yet, when put in leadership positions, they rate team building as one of the least important management skills to possess (Taylor & Stein, 2014). They have been found to be socially motivated (Gibson et al, 2009) but also more self-centered and materialistic (Twenge & Kasser, 2013).…”
Section: Millennials As a Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…They were found to value loyalty less than other cohorts (Gibson et al, 2009) but also to desire dedication for their supervisors and their employers (Sessa et al, 2007). Millennials seem to enjoy collaboration and value being on teams (Maier et al, 2015), yet, when put in leadership positions, they rate team building as one of the least important management skills to possess (Taylor & Stein, 2014). They have been found to be socially motivated (Gibson et al, 2009) but also more self-centered and materialistic (Twenge & Kasser, 2013).…”
Section: Millennials As a Cohortmentioning
confidence: 99%
“…Not all extant research is supportive of negative stereotypes, however. Others have found that this cohort prefers to be included in decision‐making, seeking opportunities to question policies, interact directly with leadership, participate in making critical decisions, collaborate with peers, and spend their time working on tasks that have real‐world impact (Maier, Tavanti, Bombard, Gentile, & Bradford, ). In direct contrast with Twenge et al's () finding regarding extrinsic reward preferences, Kroth and Young () found evidence that millennials seem to favor intrinsic factors related to organizational culture (e.g., interaction with peers and opportunities for skill development) while discounting more extrinsic concerns (e.g., job location and compensation).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a cloud leader who attempts to "bring out" the positive in each person and who looks for the opportunities that will improve their capabilities can have long lasting effects on millennial individuals. Maier et al (2015) studied millennial generation hospitality students and their perceptions of value-centered leadership principles. They proposed that it will be beneficial if leaders leading millennials consider the following recommendations: 1) forming team-based workgroups with a mentor that guides their work with…”
Section: Millennial Generationmentioning
confidence: 99%
“…Based on the birth cohort perspective, differences among three age cohorts ("Baby Boomers": 1945-1964; "Gen X": 1965-1980; "Gen Y/Gen Me/Nexters/Millenialls": >1980) have been explored from: (a) frontline and service contact employee perspectives [72][73][74]; (b) managerial perspectives [75]; and (c) the perspectives of both groups of employees' and managers [76][77][78][79][80][81] (except housekeeping [82]). Students' perspectives on work values and their career expectations have been explored in terms of understanding the entrants' (Gen Y) ways of thinking on arrival in the tourism and hospitality labor market (e.g., [83][84][85][86][87][88][89][90][91]). …”
Section: Generational Perspectives On Employment and Sustainability Imentioning
confidence: 99%